Experimental adaptation to marine conditions by a freshwater alga. (1st October 2015) - Lachapelle, Josianne; Bell, Graham; Colegrave, Nick
Abstract: The marine‐freshwater boundary has been suggested as one of the most difficult to cross for organisms. Salt is a major ecological factor and provides an unequalled range of ecological opportunity because marine habitats are much more extensive than freshwater habitats, and because salt strongly affects the structure of microbial communities. We exposed experimental populations of the freshwater alga Chlamydomonas reinhardtii to steadily increasing concentrations of salt. About 98% of the lines went extinct. The ones that survived now thrive in growth medium with 36 g⋅L −1 NaCl, and in seawater. Our results indicate that adaptation to marine conditions proceeded first through genetic assimilation of an inducible response to relatively low salt concentrations that was present in the ancestors, and subsequently by the evolution of an enhanced inducible response to high salt concentrations. These changes appear to have evolved through reversible and irreversible modifications, respectively. The evolution of marine from freshwater lineages is an example that clearly indicates the possibility of studying certain aspects of major ecological transitions in the laboratory.